2021
DOI: 10.1016/j.lanwpc.2021.100162
|View full text |Cite
|
Sign up to set email alerts
|

The impacts of New Zealand's COVID-19 epidemic response on community antibiotic use and hospitalisation for pneumonia, peritonsillar abscess and rheumatic fever

Abstract: Background The rate of community antibiotic use in New Zealand (NZ) is high and some may be unnecessary. Non-pharmaceutical public health interventions (Alert Levels) were implemented in 2020 to reduce the spread of COVID-19 in NZ and were likely to have affected antibiotic prescribing. Methods We aimed to identify the impact of these public health interventions on community antibiotic dispensing. We also examined rates of hospitalisation with infectious diseases that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
15
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 9 publications
4
15
0
5
Order By: Relevance
“…Esta tendencia se detecta en otros países, como Reino Unido o Portugal 18 , 19 , con un sistema sanitario parecido al nuestro y en otros continentes 20 , 21 , 22 . En un estudio del ámbito de AP 18 , la prescripción se redujo un 15,48% en el periodo de abril a agosto de 2020 respecto al mismo periodo de 2019, aunque, teniendo en cuenta el descenso experimentado en el número de consultas, consideran que el número de prescripciones fue un 6,71% mayor que el esperado.…”
Section: Discussionunclassified
See 2 more Smart Citations
“…Esta tendencia se detecta en otros países, como Reino Unido o Portugal 18 , 19 , con un sistema sanitario parecido al nuestro y en otros continentes 20 , 21 , 22 . En un estudio del ámbito de AP 18 , la prescripción se redujo un 15,48% en el periodo de abril a agosto de 2020 respecto al mismo periodo de 2019, aunque, teniendo en cuenta el descenso experimentado en el número de consultas, consideran que el número de prescripciones fue un 6,71% mayor que el esperado.…”
Section: Discussionunclassified
“…En el estudio realizado en Nueva Zelanda 20 se concluye que, a pesar de la marcada reducción en la dispensación comunitaria de antibióticos observada durante la implementación de intervenciones de salud pública no farmacológicas para frenar la COVID-19, no hubo un aumento en las tasas de hospitalización por infecciones centinela que el uso de antibióticos en la comunidad podrían prevenir.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…A clear seasonal pattern was observed with dispensing rates, highest in summer and autumn [ 31 ]. A recent NZ study compared antimicrobial dispensing before and after public health interventions were introduced in 2020 to reduce the spread of COVID-19 [ 32 ]. Duffy et al [ 32 ] found antimicrobial dispensing reduced by 36% during COVID alert levels 3 and 4 (lockdown).…”
Section: Human Use Of Antimicrobials In New Zealandmentioning
confidence: 99%
“…A recent NZ study compared antimicrobial dispensing before and after public health interventions were introduced in 2020 to reduce the spread of COVID-19 [ 32 ]. Duffy et al [ 32 ] found antimicrobial dispensing reduced by 36% during COVID alert levels 3 and 4 (lockdown). These reductions were mainly seen for antimicrobials used to treat respiratory and urinary tract infections—but hospital admissions due to these infections did not increase.…”
Section: Human Use Of Antimicrobials In New Zealandmentioning
confidence: 99%